2017
DOI: 10.1080/2055074x.2016.1262569
|View full text |Cite
|
Sign up to set email alerts
|

SAPO-37 microporous catalysts: revealing the structural transformations during template removal

Abstract: We have studied the structural behavior of SAPO-37 during calcination using simultaneous in situ powder X-ray diffraction (PXRD) and mass spectroscopy (MS) in addition to ex situ thermogravimetric analysis (TGA) and differential scanning calorimetry (DSC). A spike in the unit cell volume corresponding to template removal (tracked using the occupancy of the crystallographic sites in the SAPO-37 cages) is revealed from the XRD data and is strongly correlated with the DSC curve. The occupancy of the different tem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(24 citation statements)
references
References 38 publications
2
21
0
Order By: Relevance
“…suggested that if Al−O−P bonds were broken, a 31 P peak would appear at δ =−15 ppm from hydrolyzed P atoms . Thus, it appears that no Al−O−P bonds are broken at RT, in contrast to other template‐free SAPO frameworks such as SAPO‐37 . Upon increasing the temperature to 100 °C, all changes occur within 1 h. The two 27 Al NMR and 31 P NMR spectra at 100 °C were acquired after stabilization of the sample.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…suggested that if Al−O−P bonds were broken, a 31 P peak would appear at δ =−15 ppm from hydrolyzed P atoms . Thus, it appears that no Al−O−P bonds are broken at RT, in contrast to other template‐free SAPO frameworks such as SAPO‐37 . Upon increasing the temperature to 100 °C, all changes occur within 1 h. The two 27 Al NMR and 31 P NMR spectra at 100 °C were acquired after stabilization of the sample.…”
Section: Resultsmentioning
confidence: 99%
“…[12b] Thus, it appears that no AlÀOÀPb onds are broken at RT,i nc ontrast to other template-free SAPO frameworks such as SAPO-37. [16] Upon increasing the temperature to 100 8C, all changes occur within 1h.T he two 27 Al NMR and 31 PNMR spectra at 100 8Cw ere acquired after stabilization of the sample. The Al and PTatomsh ave now lost the strongly coordinating water molecules:t he Al peak at d = À15 ppm disappears and the skew peak at d = 44 ppm moves to d = 36 ppm.…”
Section: In Situ Nmr Spectroscopymentioning
confidence: 99%
See 1 more Smart Citation
“…Difference Fourier maps were used to assign the positions of dummy carbon atoms to each coke position in the framework channels, see S.I. Their individual occupancies were refined (with symmetry constraints) during subsequent cycles 14,[20][21] . This is related to the changes in intensity upon deactivation mentioned above.…”
mentioning
confidence: 99%
“…However, sometimesc alcination destroys the pore structure, thus limiting the application of the materials.F or instance, the structure of FAU-types ilicoaluminophosphate zeolite SAPO-37 collapsed after the SDA tetramethylammonium hydroxide (TMAOH) was removed. [19] Solvent extractioni sa na lternative method to remove neutral and ion-paired templates in porous materials. [21] It is often used in producing mesoporous materials such as MCM-41 [22] and SBA-15.…”
Section: Introductionmentioning
confidence: 99%